Speech perception performance in experienced cochlear-implant patients receiving the SPEAK processing strategy in the Nucleus Spectra-22 cochlear implant. - Parkinson AJ; Parkinson WS; Tyler RS; Lowder MW; Gantz BJ (Journal of Speech, Language & Hearing Research, 1998)
Sixteen experienced cochlear implant patients with a wide range of speech-perception abilities received the SPEAK processing strategy in the Nucleus Spectra-22 cochlear implant. Speech perception was assessed in quiet and in noise with SPEAK and with the patients' previous strategies (for most, Multipeak) at the study onset, as well as after using SPEAK for 6 months. Comparisons were made within and across the two test sessions to elucidate possible learning effects. Patients were also asked to rate the strategies on seven speech recognition and sound quality scales. After 6 months' experience with SPEAK, patients showed significantly improved mean performance on a range of speech recognition measures in quiet and noise. When mean subjective ratings were compared over time there were no significant differences noted between strategies. However, many individuals rated the SPEAK strategy better for two or more of the seven subjective measures. Ratings for 'appreciation of music' and 'quality of my own voice' in particular were generally higher for SPEAK. Improvements were realized by patients with a wide range of speech perception abilities, including those with little or no open-set speech recognition.